Design and synthesis of novel quinazolinone–chalcone hybrids as potential apoptotic candidates targeting caspase-3 and PARP-1: in vitro, molecular docking, and SAR studies. (20th October 2022) - Madbouly, Eman A.; Lashine, El-Sayed M.; Al-Karmalawy, Ahmed A.; Sebaiy, Mahmoud M.; Pratsinis, Harris; Kletsas, Dimitris; Metwally, Kamel
Abstract : Novel quinazolinone–chalcone hybrids as potential apoptotic candidates targeting caspase-3 and PARP-1. Abstract : A new series of thirty-one quinazolinone–chalcone hybrid molecules 13–43 were designed, synthesized, and structurally characterized by different spectroscopic techniques. All the synthesized compounds were investigated for in vitro cytotoxic activity against five human cancer cell lines namely, epidermoid carcinoma A431, lung adenocarcinoma A549, fibrosarcoma HT-1080, mammary adenocarcinoma MDA-MB-231, and prostate adenocarcinoma PC-3, as well as normal AG01523 cells using the MTT assay. Most of the new hybrids showed remarkable cytotoxic activity in the low micromolar range. Compounds 20, 22, 28, 33, 39, 40, and 41 had shown the highest cytotoxicity among the tested compounds against the epidermoid carcinoma A431 with IC50 ranging from 1 to 2 μM. Notably, the tested compounds displayed no or little cytotoxicity against the normal human skin fibroblasts. Moreover, flow cytometric cell cycle analysis performed on A431 cells revealed that the most cytotoxic compounds arrested A431 cells in the S- or G2/M-phase or both and induced a marked increase in the percentage of subdiploid events, indicating the stimulation of cell death by apoptosis. A further mechanistic study demonstrated that quinazolinone–chalcone hybrids induced apoptosis via induction of caspase-3 and PARP-1 cleavage. Moreover, a molecular docking study was performed for the target chalcones to investigate their mode of binding to PARP-1. Finally, a conclusive structure–activity relationship (SAR) study was formulated to facilitate the future design of powerful apoptotic candidates targeting both caspase-3 and PARP-1 proteins.